THE POLITICS OF TRIBAL DEVELOPMENT IN INDIA: A CRITICAL STUDY ON POLICY AND PRACTICE - Padvi, Jayesh Vikram (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This research paper presents a comprehensive, evidence-based analysis of tribal development politics in post-colonial India, with particular empirical focus on Maharashtra as a representative case study. Despite seven decades of constitutional safeguards and numerous welfare schemes under the Tribal Sub-Plan strategy, India’s Scheduled Tribes (Adivasis) remain entrenched as the nation’s most marginalized demographic, exhibiting systemic exclusion across all human development indices. Through rigorous interdisciplinary methodology combining legal analysis, policy evaluation, political economy examination, and ethnographic insights, this study reveals the structural paradox between progressive legislative intent and persistent implementation failures. This research establishes three core findings: First is constitutional protections like the Fifth Schedule and PESA Act remain substantially unimplemented due to bureaucratic resistance and lack of political will. Second is tribal welfare schemes suffer from chronic design flaws including centralization, corruption, and exclusionary targeting and third is electoral politics actively perpetuates tribal marginalization through calculated vote-bank strategies rather than genuine empowerment. The study concludes with a seven-point reform agenda for transformative tribal development, emphasizing constitutionalism, participatory governance, and rights-based approaches.